KONSEP HAK MENGUASAI NEGARA TERHADAP TANAH DALAM HUKUM TANAH (UUPA) DAN KONSTITUSI - NI LUH ARININGSIH SARI (Universitas Mahasaraswati Mataram, 2021)
The concept of the State's Right to Control over Land in Land Law (UUPA) and the Constitution are things that need to be clarified based on law. The type of research in this research is normative research, namely research on legal principles related to the concept of the State's right to control over land seen from the aspects of the Basic Agrarian Law and the 1945 Constitution of the Republic of Indonesia. The approach method used in this research is the statutory approach (the statute approach), the conceptual approach, which utilizes the views and thoughts of experts regarding the concept of the rule of law and the historical approach is carried out by examining what background. which underlie a development of the implementation of the right to control the State. The results of the study show that the concept of the right to control of the State which is regulated in the 1945 Constitution and the UUPA, is different from the legal relationship which is ownership between the State and land based on the Domeinverklaring principle which is regulated in the Land Law for the Administration of the Dutch East Indies Government which has been revoked in the UUPA. The principle of Domeinverklaring contradicts the legal awareness of the Indonesian people and the principles of an independent and modern State, especially in the 1945 Constitution which regulates State control of all agrarian resources which are essentially intended for the greatest prosperity of the people (Article 33 paragraph (3)).